Beyond greed and fear - Shefrin, Hersh (Harvard Business School Press, 2002)
Even the best Wall Street investors make mistakes. No matter how savvy or experienced, all financial practitioners eventually let bias, overconfidence, and emotion cloud their judgement and misguide their actions. Yet most financial decision-making models fail to factor in these fundamentals of human nature. In Beyond Greed and Fear, the most authoritative guide to what really influences the decision-making process, Hersh Shefrin uses the latest psychological research to help us understand the human behavior that guides stock selection, financial services, and corporate financial strategy. Shefrin argues that financial practitioners must acknowledge and understand behavioral finance--the application of psychology to financial behavior--in order to avoid many of the investment pitfalls caused by human error